Hubungan Support System Keluarga dengan Tingkat Kecemasan pada Anak Praseolah Akibat Hospitalisasi di RSU Imelda Pekerja Indonesia Medan - Ito, Mita Melinda (LPPM Institut Kesehatan Helvetia, 2019)
Hospitalization in children is a process because of a planning or emergency reason that requires the child to stay in the hospital to undergo therapy and treatment until returning home. During the process, the child can experience psychological changes such as feelings of fear, sadness and anxiety. Based on the preliminary survey data on 15 children at Imelda Pekerja Indonesia found 6 children experienced in mild anxiety, while l 2 children experienced in severe anxiety while the support of good families was 4 people and less than 11 people. The aim of this research was to find out the relationship offamily support system with the level of anxiety in preschool children due to hospitalization at Imelda Pekerja Indonesia General Hospital Medan Indonesia. The method used in this study was an analytical survey with a cross sectional approach. The populations in this study were all children who were treated at the Imelda Pekerja Indonesian in 2018 were 32 people while the samples in this study were all children treated amount 32 people at Imelda Pekerja Indonesian General Hospital 2018. The technique sampling used in this study was the total sampling techniques and the test was do e by using chi-square test. Based on the results of statistical tests at 95% confidence level obtained p =0.023 from a = 0.05. These results prove that there was a relationship offamily support systems and the level of anxiety in preschool children due to hospitalization. The conclusion in this study shows that there is a relationship of family support system with the level of anxiety in preschool children due to hospitalization. It is suggested to the health workers to always provide information and counseling to families about family support systems and child anxiety.